Ground-truthing political elites in the public sphere: Measuring the arena effects of elite opinion - Tim Henrichsen; Philip Leifeld; Lorien Jasny; Iain Weaver; Dana R. Fisher (Research & Politics)
Political elites express their ideological positions on contentious issues across various arenas in the public sphere. Social science research often relies on data extracted from various media or political and administrative sources, as well as surveys that are administered directly with the political actor. Although some studies compare ideology across different sources, few systematically analyze how political actors adjust their ideological messaging to the audiences in the respective communication arenas and how such changes are associated with systematic bias in data sources. This paper uses a unique dataset combining climate policy belief observations from three arenas—social media, Congressional testimony, and surveys—on identical ideological variables and during the same time period. We apply item response theory to understand how responses differ by arena and find that ideological communication on Twitter is most left-leaning, Congressional testimony is most right-leaning, and surveys, the data source with the smallest potential arena effect, is in the middle. We also find that actors with strong ideological leaning moderate their positions on social media and in Congress. These findings enhance our understanding of strategic communication depending on audience context and inform social research on biases when analyzing specific data sources.